1996
DOI: 10.1007/bf00224098
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Meloidogyne incognita resistance genes in Lycopersicon peruvianum differentiated by heat sensitivity and nematode virulence

Abstract: Resistance to Meloidogyne incognita (Kofoid and White) Chitwood in clones of Lycopersicon peruvianum (L.) Mill. PI 126443-1MH, 270435-2R2 and 2704353MH, their F1, a field-produced F2, and their test-cross (TC1) populations, was evaluated based on egg masses and eggs produced on root systems. Reactions to M. incognita isolates differing in virulence to gene Mi were determined at 25°C (Mi expressed) and 32°C (Mi not expressed). PI 126443-1MH, 270435-2R2, 270435-3MH, and their F1 progenies were resistant to Mi-vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0
4

Year Published

1997
1997
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 15 publications
0
31
0
4
Order By: Relevance
“…Several L. peruvianum accessions have been identified to possess heat-stable resistance (Ammati et al 1986;Veremis and Roberts 1996b). L. peruvianum is cross-incompatible with cultivated tomato, L. esculentum, thus impeding efforts to introgress the resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Several L. peruvianum accessions have been identified to possess heat-stable resistance (Ammati et al 1986;Veremis and Roberts 1996b). L. peruvianum is cross-incompatible with cultivated tomato, L. esculentum, thus impeding efforts to introgress the resistance.…”
Section: Introductionmentioning
confidence: 99%
“…For example, new sources of root-knot nematode resistance have been identified in accessions of S. peruvianum (Ammati et al, 1985(Ammati et al, , 1986. Inheritance studies of some of these new resistance traits have revealed the presence of additional genes that segregate independently of Mi-1 (Cap et al, 1993;Veremis and Roberts, 1996b). These genes were distinguished according to resistance phenotype at high temperature or resistance to Mi-1-virulent nematode isolates Roberts, 1996a, 1996b).…”
mentioning
confidence: 99%
“…However, Veremis and Roberts (1996) suggested that the two phenotypes were controlled by linked genes, Mi-3 and Mi-5. Possible explanations for the discrepancy with our results include differences in the backgrounds of the parental lines or resistance assay procedures.…”
Section: Discussionmentioning
confidence: 99%
“…The resistance gene, Mi-3, which confers resistance to Mi-1-virulent root-knot nematode strains, has been mapped to the short arm of chromosome 12 (Yaghoobi et al 1995;Huang et al 2004). In addition, Mi-3, or a closely linked gene, confers resistance at temperatures above 30°C (Yaghoobi et al 1995;Veremis and Roberts 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation